2022
DOI: 10.1177/1934578x211069721
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Review of Phenolic Compounds Identified from Plants: Their Extraction, Analysis, and Biological Activity

Abstract: Phenolic compounds are the most abundant secondary metabolites in plants, showing a wide range of distinct biological activities, have received more and more attention in recent years. This review aims to gather and systematize available information on the phenolic compounds from plants by discussing different types of phenolic compounds, extraction, and analysis methods, with an emphasis on their potential biological activities. The research direction and problems that should be paid attention to in the futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
114
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(120 citation statements)
references
References 125 publications
(151 reference statements)
2
114
0
4
Order By: Relevance
“…The high structural and physicochemical diversity of natural molecules produced by plants, microorganisms, and insects makes them a virtually inexhaustible source with potential for the discovery and development of novel bioactive compounds with applications in the pharmaceutical, food, and biotechnological industries, to name only a few [238,239]. Additionally, the selectivity, specificity, and potency are common features of many natural compounds as the result of their ongoing evolutionary specialization over [198,199,204] Well diffusion method Diffusion of a liquid antimicrobial agent placed in a well punched into the solid culture medium that has been seeded with a pure culture…”
Section: Discussionmentioning
confidence: 99%
“…The high structural and physicochemical diversity of natural molecules produced by plants, microorganisms, and insects makes them a virtually inexhaustible source with potential for the discovery and development of novel bioactive compounds with applications in the pharmaceutical, food, and biotechnological industries, to name only a few [238,239]. Additionally, the selectivity, specificity, and potency are common features of many natural compounds as the result of their ongoing evolutionary specialization over [198,199,204] Well diffusion method Diffusion of a liquid antimicrobial agent placed in a well punched into the solid culture medium that has been seeded with a pure culture…”
Section: Discussionmentioning
confidence: 99%
“…Among the diverse and complex groups of phenolics that include simple phenols, flavonoids, stilbenes, tannins, and others, phenolic acids are the most distributed in nature. They have been found in various plants, fruits, vegetables, beverages, and agro-food by-products where they contribute to organoleptic attributes such as color, flavor, and odor but their true merits are numerous positive biological activities such as antibacterial, anti-inflammatory, antiallergenic, anticancer, cytotoxic, antitumor, cardioprotective, and antioxidant, which is among the most investigated [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…These properties presented them as major compounds in the prevention and treatment of chronic disease including cancer, cardiovascular disease (CVD), neurodegenerative disorders, diabetes, and renal failure [ 24 , 25 , 26 , 27 ]. Phenolic compounds are extensively distributed in plants and exhaustive studies demonstrated their benefits and curative potential, including antioxidant, anti-microbe, anti-neoplasic, and anti-inflammatory effects [ 28 , 29 , 30 , 31 , 32 ]. Phenolic compounds in foods such as naringin, quercetin, and chlorogenic acid has been found in a variety of herbs and fruits.…”
Section: Introductionmentioning
confidence: 99%